Fostering collaborative practice: a pilot study on interprofessional education through simulation-based team-oriented learning sessions among pharmacy and medical students - Shaimaa Khamis Mostafa; Rania H. Abdel-Rahman; Ahmed K. Mansour; Magda A. El-Sherbeny (Discover Education)
Abstract Background It is pivotal to implement effective collaboration among professionals from different disciplines in the healthcare sector. As the complexity of patients’ health needs grows, so does the importance of developing innovative and efficient models of patient care that rely on interprofessional collaborative teamwork. Interprofessional education (IPE) is a valuable approach that improves communication, collaboration, and ultimately safe patient outcomes in healthcare settings. Students studying medicine and pharmacy are among the healthcare professionals who could potentially benefit from IPE. Despite the existence of newly added undergraduate curricula for interprofessional communication and professionalism, active implementation to achieve the required competencies and skills is not yet widespread, particularly in developing countries. This article presents a successful implementation of simulation-based team-oriented learning sessions among pharmacy and medical students at Delta University for Science and Technology in Egypt. The purpose of the IPE activity was to train students to work collaboratively as members of an interprofessional healthcare team by simulating a real-life situation. Results Student feedback was very positive with most pharmacy and medical students being satisfied with their IPE experience. Moreover, students’ feedback emphasized the significance of IPE and a simulated team-based environment in improving communication skills and collaborative practice. Conclusion The high level of student satisfaction with the IPE sessions, particularly regarding the clarity of training objectives and the interactive nature of the experience, suggests that simulation-based learning is an effective tool for developing key interprofessional collaboration skills among healthcare students. This highlights the potential of IPE to cultivate future healthcare professionals who excel in interprofessional collaboration, ultimately leading to improved patient care and outcomes. Overcoming barriers to implementing IPE in Egypt needs a multifaceted strategy and a comprehensive long-term follow-up plan is critical for evaluating the lasting effect of IPE on students’ collaborative practices in real-life healthcare settings.